Hematopoietic Cell Transplantation for MHC Class II Deficiency - Lum, Su Han; Neven, Benedicte; Slatter, Mary A.; Gennery, Andrew R. (Frontiers in Pediatrics, 2019)
Major histocompatibility complex (MHC) class II deficiency is a rare and fatal primary combined immunodeficiency. It affects both marrow-derived cells and thymic epithelium, leading to impaired antigen presentation by antigen presenting cells and delayed and incomplete maturation of CD4+ lymphocyte populations. Affected children are susceptible to multiple infections by viruses, Pneumocystis jirovecii, bacteria and fungi. Immunological assessment usually shows severe CD4+ T-lymphocytopenia, hypogammaglobulinemia and lack of antigen-specific antibody responses. The diagnosis is confirmed by absence of constitutive and inducible expression of MHC class II molecules on affected cell types which is the immunologic hallmark of the disease. Haematopoietic cell transplantation (HCT) is the only established curative therapy for MHC class II deficiency but it is difficult as affected children have significant comorbidities at the time of HCT. Optimization organ function, implementing a reduced toxicity conditioning regimen, improved T-cell depletion techniques using serotherapy and graft manipulation, vigilant infection surveillance, pre-emptive and aggressive therapy for infection and newer treatments for graft-versus-host disease have improved the transplant survival for children with MHC class II deficiency. Despite persistent low CD4+ T-lymphopenia reported in post-HCT patients, transplanted patients show normalization of antigen-specific T-lymphocyte stimulation and antibody production in response to immunization antigens. There is a need for a multi-centre collaborative study to look at transplant survival of HCT and long-term disease outcome in children with MHC class II deficiency in the modern era of HCT.